On the syntax of comitative constructions: the case of Finnish mukana, mukaan ‘with, along’ - Ojutkangas Krista (Estonia, 2022)
The topic of this article is the syntax of Finnish comitative markers mukana and mukaan ‘with, along’. Comitative markers express accompaniment relations, which are typically conceived of being asymmetrical: the accompanee is the predominant participant, while the companion is involved in the situation only via the accompanee (Stolz et al. 2006: 26–27). However, markers such as mukana and mukaan are used in several syntactic constructions where the grammatical roles of expressions of the accompanees vary from subject to adverbial, that is, from syntactic core to periphery. Five syntactic construction types were analyzed from a corpus data showing three genres. On the basis of this study, it is shown that syntactic variation has an effect on the conceived asymmetry between the accompanee and the companion, and that syntax makes an important contribution to the semantics of comitative constructions. In strongly asymmetric accompaniment relations, a human accompanee is expressed by a possessive suffix affixed to the comitative marker, or by a clause-initial adverbial. The question of asymmetry contracts to the background when the accompanee is expressed by a non-clause-initial adverbial and when the accompanee is implicit, without overt marking altogether.